Uncomfortable realities: the challenge of creating real change in Europe's consolidating hospital sector. Issue 2 (May 2016) - Jeurissen, Patrick; Duran, Antonio; Saltman, Richard
Abstract Background This article examines uncomfortable realities that the European hospital sector currently faces and the potential impact of wide-spread rationalization policies such as (hospital) payment reform and privatization. Methods Review of relevant international literature. Results Based on the evidence we present, rationalization policies such as (hospital) payment reform and privatization will probably fall short in delivering better quality of care and lower growth in health expenses. Reasons can be sought in a mix of evidence on the effectiveness of these rationalization policies. Nevertheless, pressures for different business models will gradually continue to increase and it seems safe to assume that more value-added process business and facilitated network models will eventually emerge. Conclusions The overall argument of this article holds important implications for future research: how can policymakers generate adequate leverage to introduce such changes without destroying necessary hospital capacity and the ability to produce quality healthcare.